Role of mass media in disseminating knowledge about Tuberculosis among the attendants accompanying patients of a tertiary care hospital of Bangladesh - Nowshin, Iffat; Alima, Fouzia; Chowdhury, Md Iqbal Bahar; Ahmed, Mahmuda (Northern International Medical College Journal, 2021)
Background : Tuberculosis (TB) is a major public health problem in Bangladesh. The use of mass media is one of the important strategies in communicating behavioural change in relation to TB prevention and the treatment. However, most of the mass media public health interventions do not sufficiently engage the people. Due to this, truly little is known about the effects of locally instigated mass media promotion. Objective : To explore role of mass media on knowledge generation about Tuberculosis transmission in Bangladesh. Methods : This cross-sectional study was conducted among 180 adult persons(attendants of patients) of different socio-economic backgrounds attending the outpatient’s departments(OPD) of a tertiary care hospital. Purposive sampling was the process of selecting the subjects. Data were collected using one pretested semi-structured questionnaire through face-to-face interview. Results : A total180 respondents were interviewed. Mean age of the respondents was 28.75 ± 8.55 years. Majority of the respondents were graduate (29.0%).A total of 20.2% respondents had adequate knowledge about TB transmission without any misconceptions. Similarly, regarding the misconceptions on modes of TB transmission, 40.5% replied that TB transmits through utensils,57.6% respondents replied that TB transmits through sharing clothes/bed sheets/towel. About 28.3% respondents had the perception that the cost of TB treatment is high. Among the respondents30.5% had the false perception that it was necessary to go to big hospitals for TB treatment. Highest 140 (77.8%) respondents said television as the source of information in TB prevention. Friends/ relatives/ teachers, newspaper, radio, billboard etc. were the other sources. Twenty did not hear of TB prevention program. Conclusion : The mass media can be effective in getting messages about TB across to the community in developing countries. In this study we found that television, newspapers, and billboards were particularly useful tools for reaching out to them with specific campaigns regarding TB control. Northern International Medical College Journal Vol.11 (2) Jan 2020: 463-467